2019
DOI: 10.1128/iai.00583-18
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Roles for Interleukin-36 Cytokines in Protective Host Defense against MurineLegionella pneumophilaPneumonia

Abstract: Legionella pneumophila causes life-threatening pneumonia culminating in acute lung injury. Innate and adaptive cytokines play an important role in host defense against L. pneumophila infection. Interleukin-36 (IL-36) cytokines are recently described members of the larger IL-1 cytokine family known to exert potent inflammatory effects. In this study, we elucidated the role for IL-36 cytokines in experimental pneumonia caused by L. pneumophila. Intratracheal (i.t.) administration of L. pneumophila induced the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…These data, suggesting that IL-36α plays a potential role in the development of A. fumigatus keratitis, are consistent with results in a previous study from another laboratory indicating that IL-36α was induced after infection and correlated with the development of Legionella pneumophila pneumonia. 17 This was further confirmed by an in vitro study that reported that the expression of IL-36α was significantly increased in the primary macrophages stimulated with A. fumigatus hyphae.…”
Section: Discussionmentioning
confidence: 65%
“…These data, suggesting that IL-36α plays a potential role in the development of A. fumigatus keratitis, are consistent with results in a previous study from another laboratory indicating that IL-36α was induced after infection and correlated with the development of Legionella pneumophila pneumonia. 17 This was further confirmed by an in vitro study that reported that the expression of IL-36α was significantly increased in the primary macrophages stimulated with A. fumigatus hyphae.…”
Section: Discussionmentioning
confidence: 65%
“…IL-36 cytokines are major effectors of the immune response in the lungs during P. aeruginosa and other bacterial infections ( 30 , 31 , 34 ). Il36a transcript level was increased in the lungs by 1 dpi ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Neutralizing anti-IL-36γ antibody was generated in New Zealand White rabbits that were immunized with recombinant mouse IL-36γ ( 30 , 34 ). The antibody was purified and measured for titer by ELISA ( 30 , 34 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, IL-36 has been shown to be important in a number of infections at different mucosal sites. At these surfaces, it induces a series of different AMPs and other protective factors, including peptidoglycan recognition protein 2, human β-defensin 2, or matrix metallopeptidase 9 (Huynh et al, 2016;Aoyagi et al, 2017;Kovach et al, 2017;Nanjo et al, 2018;Scholz et al, 2018;Heath et al, 2019).…”
Section: Role Of Il-36 Cytokines In Anti-candida Responsesmentioning
confidence: 99%